TEKNIK CUT THINK POINT EDITING PADA PRODUKSI FEATURE â€œRAMBATING SUMBUTâ€ - Fadeyanto Prabowo, Asniyati Hanifah Dwi Nurrahmi K (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACTRAMBATING SUMBUT, is a feature program explained about the regeneration of farmers. Agricultural sector hold the main role in human living, especially as the supplier of foods and the mover of economic wheels. However, at the present time, agricultural sector is only rest on farmers aged above 45 years old. Feature RAMBATING SUMBUT has message that the key of living is on the agricultural sector. Hence, it is very important for young generations to be taught on how right farming is, even with the advanced technology so they can be promising farmers. Therefore, the agricultural sector will be a promising field for young generations and they will proud of it as the agricultural sector is continuing for generations. In the production of RAMBATING SUMBUT feature, the writer of this study used Cut Think Point Editing which choosing, cutting, and combining shots are not just merely cinematic mechanism technical but also considering the sense. Some things should be noticed before doing cutting shots are the composition, images continuity, and some aspects of combining images (spatial, rhythmic, tempo, and space). Keywords: Cut Think Point, Editing, Feature, Farmers? Regenerations.